The impact of product quality and service quality on consumer loyalty (case study of Bandeng Rozal in Bandengan village, Kendal district, Kendal regency) - Mawadah Murtiawati; Zuhdan Ady Fataron (Journal of Islamic Economics, Management, and Business (JIEMB), 2019)
Purpose - The purpose of this research is to test the quality of products and quality of service to consumer loyalty of small business, Bandeng Rozal.Method - Data were obtained from distributing questionnaires to 100 consumers using simple random sampling and measured by the scale of Likert. Quantitative analysis included validity and reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing through t-test and F test, and analysis of the coefficient of determination (R2), while data processing is run used SPSS 16.Result - The result showed the variables in this research had a significant effect on consumer loyalty. Based on the F test, it showed that variables in this study in which they were product quality and service quality simultaneously or jointly have a significant effect on consumer loyalty.Implication - This result can assist small business in increasing their consumer loyalty.Originality - This research focuses on small business adaptability in competing in the industry with a marketing perspective.